(x-2)(-2x+1)=0

Simple and best practice solution for (x-2)(-2x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(-2x+1)=0 equation:


Simplifying
(x + -2)(-2x + 1) = 0

Reorder the terms:
(-2 + x)(-2x + 1) = 0

Reorder the terms:
(-2 + x)(1 + -2x) = 0

Multiply (-2 + x) * (1 + -2x)
(-2(1 + -2x) + x(1 + -2x)) = 0
((1 * -2 + -2x * -2) + x(1 + -2x)) = 0
((-2 + 4x) + x(1 + -2x)) = 0
(-2 + 4x + (1 * x + -2x * x)) = 0
(-2 + 4x + (1x + -2x2)) = 0

Combine like terms: 4x + 1x = 5x
(-2 + 5x + -2x2) = 0

Solving
-2 + 5x + -2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-2 + x)(1 + -2x) = 0

Subproblem 1

Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2

Subproblem 2

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Solution

x = {2, 0.5}

See similar equations:

| 6b^2+19b+15=0 | | 3.9x-6.47=2.5 | | (2x-1)(x-12)=0 | | 6y-2+8y+14+42=180 | | 3/8-1/4x5/6 | | 7+35x=15x+39 | | x^2+12m+26=0 | | 2(11x-3)=104 | | (-x+3)(3x+9)=0 | | Logx(5x-14)+logx(x-6)=2 | | 2m^2-12m+26=0 | | 8c^2=10c | | -6=-3w+8(w+3) | | james=gay | | fuck=boy | | -1=-2v+7(v+7) | | d-9=-24 | | 5x-2+7x+3y= | | 8-2x=4(x+2) | | 6y^2+5=225 | | (2x-2y)dx+(y-1)dy=0 | | 6y^2+5= | | 15x=19x-12 | | 3y-17=16 | | 8-2x=3(x+2) | | 13x-33=7-(2x-4) | | -4-12=9x+18-8x | | 3=x/2-17 | | (4x+3y-7)dx+(3x-7y+4)dy=0 | | 6(2x+4)=42 | | 2x-4+4x+10=9x-9 | | 2600+30x=2400+50x |

Equations solver categories